The Customer Caste: Lawful Discrimination by Public Businesses - Thomas, Suja A. (California law review, 2021)
It is legal to follow and watch people in retail stores based on their race, give inferior service to restaurant customers based on their race, and place patrons in certain hotel rooms based on their race. Congress enacted Title II of the Civil Rights Act of 1964 to protect Black and other people of color from discrimination and segregation in public accommodations—places where people receive goods, food, services, and lodging. Scholarship has not analyzed how well Title II and Section 1981 of the Civil Rights Act of 1866 have functioned in this arena. An examination of this caselaw shows that courts find legal numerous discriminatory and segregatory actions by places of public accommodation. An abbreviated look at Section 1982 of the Civil Rights Act of 1866 shows that courts have interpreted that law in the same manner as Section 1981. An assessment of the legislative history and text of Title II and Section 1981, in addition to a comparison to the interpretation of laws with similar purposes, demonstrates that the federal judiciary has incorrectly constrained the law by, among other actions, adopting the heavily criticized employment discrimination caselaw and requiring a common law-like contractual relationship. Jim Crow laws ceased to exist in the 1960s, but these interpretations have created “the customer caste,” whereby people of color are subject to legal, daily discrimination in retail stores, restaurants, gas stations, hotels, banks, and airplanes.